Myeloid-Derived Suppressor Cells Participate in Preventing Graft Rejection - Yan Wang; Xiaodong Gu; Jianbin Xiang; Zongyou Chen (Clinical and Developmental Immunology)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of cells and have a tremendous potential to suppress immune responses. MDSCs accumulate during tumor progression, autoimmunity, chronic infection, transplantation, and other pathological conditions and can potently suppress T-cell function. Here, we discuss recent findings that describe the molecular mechanisms of MDSCs suppressing T-cell immune responses as well as recent observations that MDSCs may have roles in transplant tolerance.